When routine screening is not routine: Preparing patients for the unexpected - Millstein, Jeffrey (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2022)
In our current environment of value based care and payment models, greater emphasis is placed on completing evidence based, routine screening tests for patients. While there is clear preventive health benefit, population based initiatives may overlook opportunities to prepare individual patients for possible abnormal results. Efforts to manage expectations, address health literacy gaps and ensure emotional support may help limit unnecessary distress and suffering during the screening process.